D. H. Lawrence in the Modern World
XVI, 221 p.
Keywords: 60 years after Lawrence's death, the nature of his achievement is still being debated. His vision has aroused passionate interest in many countries beyond his own. As a writer in the 20th century and as one with international standing, this book presents Lawrence "in the modern world".